2019
DOI: 10.2478/ausae-2019-0001
|View full text |Cite
|
Sign up to set email alerts
|

First molecular identification of wheat seed gall nematode Anguina tritici races parasitized on wheat in Iraq

Abstract: This study was conducted to identify races of wheat seed gall nematode Anguina tritici by using molecular identification for this nematode species parasitized on durum and bread wheat cultivars. Wheat seed galls of both cultivars were collected from two cities, Erbil and Duhok, from the Kurdistan Region and Iraq respectively. DNA was extracted from both nematode isolates (populations), and then PCR reactions were performed with Internal Transcribed Spacer (ITS) region using primers TW81/AB28 with 2 µl of templ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…The harvested seeds were also infected with the nematode, appearing darker, spotted on the surface, and smaller in size. Ami et al (2019) already described the presence of three biotypes of A. tritici in three legume plants with high infection rates: (i) durum wheat biotype, (ii) the bread wheat biotype, and (iii) barley biotype. In the current study, nematodes collected from infected seeds were molecularly identified in order to investigate the affinities of the recovered tentative barley biotype.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The harvested seeds were also infected with the nematode, appearing darker, spotted on the surface, and smaller in size. Ami et al (2019) already described the presence of three biotypes of A. tritici in three legume plants with high infection rates: (i) durum wheat biotype, (ii) the bread wheat biotype, and (iii) barley biotype. In the current study, nematodes collected from infected seeds were molecularly identified in order to investigate the affinities of the recovered tentative barley biotype.…”
Section: Resultsmentioning
confidence: 99%
“…In Iraq, it has already reported from wheat-growing areas ( Rao, 1921 ; ­Al-Bedawi et al, 1977; Ami and Taher, 2013 ; Ami et al, 2019 ), and its infection was estimated around 22.9%, causing 30% crop losses ( Al-Beldawi et al, 1977 ; Stephan and Antoon, 1990 ). In the last decades, the wheat seed nematode was also found in Iraq, infecting barley with an infection rate up to 90%, suggesting the occurrence of a tentative new biotype of the nematode ( Al-Talib et al, 1986 ; Mustafa, 2009 ; Ami et al, 2019 ; Qassem et al, 2021 ). The present study aims to characterize the recently recovered population of A. tritici from barley fields in Iraq by sequencing the ribosomal ITS and the partial 18S rRNA genes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…that they could be two variants when N-J phylogenetic tree separated them into two clades within A. tritici branch [Figure 3]. Thus, SSU could be useful molecular loci for identification, differentiation, and phylogeny reconstruction of A. tritici in Iraq [8,21].…”
Section: Field Experimentsmentioning
confidence: 99%
“…It has been described for the 1 st time by Needham since 1743 [1]. Seed gall disease has been reported in Iraq for the 1 st time since 1921 [7] but the causal agent A. tritici was recently confirmed by molecular approach [8]. This disease can cause yield losses ranged 10.76-75% in wheat [9,10].…”
Section: Introductionmentioning
confidence: 99%